2012
DOI: 10.1523/jneurosci.5087-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Nonsynaptic NMDA Receptors Mediate Activity-Dependent Plasticity of Gap Junctional Coupling in the AII Amacrine Cell Network

Abstract: Many neurons are coupled by electrical synapses into networks that have emergent properties. In the retina, coupling in these networks is dynamically regulated by changes in background illumination, optimizing signal integration for the visual environment. However, the mechanisms that control this plasticity are poorly understood. We have investigated these mechanisms in the rabbit AII amacrine cell, a multifunctional retinal neuron that forms an electrically coupled network via Cx36 gap junctions. We find tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
105
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(112 citation statements)
references
References 67 publications
7
105
0
Order By: Relevance
“…Varying the strength of presynaptic activation leads to differential activation of the different types of postsynaptic AMPA receptors, depending on the degree of spillout of glutamate at these synapses. If similar mechanisms are operative at the bipolar cell inputs to AII amacrines, changes in the Ca 2ϩ permeability of AMPA receptors evoked by diabetes could influence the signaling and integrative properties of AII amacrine cells, including the activity-driven intracellular Ca 2ϩ dynamics related to regulating the strength of gap junction-mediated electrical coupling between AII amacrine cells (Kothmann et al 2009(Kothmann et al , 2012 which is likely to be an important mechanism for postreceptoral visual adaptation (reviewed by Demb 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Varying the strength of presynaptic activation leads to differential activation of the different types of postsynaptic AMPA receptors, depending on the degree of spillout of glutamate at these synapses. If similar mechanisms are operative at the bipolar cell inputs to AII amacrines, changes in the Ca 2ϩ permeability of AMPA receptors evoked by diabetes could influence the signaling and integrative properties of AII amacrine cells, including the activity-driven intracellular Ca 2ϩ dynamics related to regulating the strength of gap junction-mediated electrical coupling between AII amacrine cells (Kothmann et al 2009(Kothmann et al , 2012 which is likely to be an important mechanism for postreceptoral visual adaptation (reviewed by Demb 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Although there has been no direct observation of activity-dependent modifications of gap-junction between RGCs, some studies suggested that gap-junction strength could be modulated by dopamine, the activity of which is influenced by the luminance of the environment (Bloomfield and Volgyi 2009). Also, luminance-and activity-dependent modifications of gap-junctions between amacrine cells have been found in the retina (Bloomfield et al 1997;Kothmann et al 2012). Alternatively, there may exist other mechanisms which could generate the observed enhanced synchrony behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The AII amacrine cell is characteristically poorly coupled in prolonged, complete darkness, but develops extensive coupling with dim background light [9]. Kothmann et al [••29] found that this light-dependent enhancement in coupling is driven by glutamate spillover from On bipolar cell (either rod- or cone-driven) activity. Enhancement of coupling depends on activation of non-synaptic NMDA receptors, activation of CaM Kinase II, and phosphorylation of Cx36.…”
Section: Seeing All Of the Lightmentioning
confidence: 99%
“…This effect required activation of CaMKII and was limited to weakly coupled IO neurons. Turecek et al [••10] further found that non-synaptic NMDA receptors were closely associated with Cx36 gap junctions in the IO glomeruli, implicating a signaling pathway highly analogous to that of retinal AII amacrine cells [••29]. NMDA application induced synchrony and enhanced the amplitudes of subthreshold oscillations, revealing a mechanism by which excitatory input can enhance the synchrony of the IO network [••10].…”
Section: Timing Is Everythingmentioning
confidence: 99%